THE ROLE OF THE TEACHER IN DEVELOPING CHEMISTRY EDUCATION IN GENERAL SECONDARY SCHOOLS - Temirov , Farrux (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article discusses the role of the teacher in the development of chemistry education in general secondary schools. The issues of teachers’ professional competence, methodological skills, and the use of innovative pedagogical technologies in effective chemistry teaching are analyzed. The paper also highlights important aspects of the pedagogical activity of a modern chemistry teacher and presents a teacher model that contributes to the development of students’ scientific thinking and increases their interest in the subject.